Bridging the gap between energy and the environment. (May 2016) - Holland, Robert A.; Scott, Kate; Hinton, Emma D.; Austen, Melanie C.; Barrett, John; Beaumont, Nicola; Blaber-Wegg, Tina; Brown, Gareth; Carter-Silk, Eleanor; Cazenave, Pierre; Eigenbrod, Felix; Hiscock, Kevin; et al.
Abstract: Meeting the world's energy demand is a major challenge for society over the coming century. To identify the most sustainable energy pathways to meet this demand, analysis of energy systems on which policy is based must move beyond the current primary focus on carbon to include a broad range of ecosystem services on which human well-being depends. Incorporation of a broad set of ecosystem services into the design of energy policy will differentiates between energy technology options to identify policy options that reconcile national and international obligations to address climate change and the loss of biodiversity and ecosystem services. In this paper we consider our current understanding of the implications of energy systems for ecosystem services and identify key elements of an assessment. Analysis must consider the full life cycle of energy systems, the territorial and international footprint, use a consistent ecosystem service framework that incorporates the value of both market and non-market goods, and consider the spatial and temporal dynamics of both the energy and environmental system. While significant methodological challenges exist, the approach we detail can provide the holistic view of energy and ecosystem services interactions required to inform the future of global energy policy. Highlights: Obligations for climate, biodiversity and ecosystem services must be aligned. Ecosystem service based assessments of energy systems can inform energy policy. Assessment to incorporate life cycle stages across spatial and temporal scales. Implications for ecosystem services differentiate between energy options. Pathways to decarbonisation should be identified based on such a holistic assessment.